MANAJEMEN MUTU TENAGA PENDIDIK ISLAM DALAM MENINGKATKAN KEPUASAN STAKEHOLDER: KAJIAN SYSTEMATIC LITERATURE - Diana Nafisa Sabilahaq; Faqih Mubarok (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
early childhood science process skills. In the midst of science learning methods that are still dominated by theory, hydroponic experimentation offers an innovative approach that provides direct, hands-on learning experiences for children. Through this method, children are encouraged to actively explore scientific concepts, increase their curiosity, and develop an understanding of plant growth processes.The aim of this study is to determine the effect of hydroponic experimentation on the science process skills of children at Kemala Bhayangkari 03 Alai Kindergarten. The research employs a quantitative approach using a Quasi-Experimental design. The population consists of 30 children, with purposive sampling used to select two groups: the experimental class (12 children) participating in hydroponic activities, and the control class (12 children) engaging in conventional learning through color mixing experiments.Data analysis was conducted using prerequisite tests and the independent sample t-test with the assistance of SPSS 23.0 for Windows. The results showed that the average pre-test score in the experimental class increased from 12.08 to 21.83 in the post-test. In the control class, scores increased from 10.33 to 18.17. Although the significance value (0.064) indicates no statistically significant difference between the two groups (p > 0.05), the greater improvement in the experimental class suggests that hydroponic experimentation has a positive impact on children's science process skills.